Applying Simple Multi Attribute Rating Technique (SMART) Method for Employee Performance Assessment - Veti Apriana; Sifa Fauziah (Institute of Computer Science (IOCS), 2022)
Employee performance appraisal is an absolute thing done by every company, in order to evaluate the performance results of the workers in the company. In addition, performance evaluation is also to determine the ability, progress and achievement or performance results of each employee. However, sometimes, in evaluating employee performance, things are often found that cause the assessment to be inaccurate, such as an assessment that is only based on employee behavior at a glance (not comprehensive) so that it is not optimal in its implementation. Based on these problems, it is necessary to have a decision support system that can help managers make decisions in evaluating employee performance, one of which is by applying the Simple Multi Attribute Rating Technique (SMART) method, a method for dealing with multi-criteria problems in a decision support system with the same criteria. used includes ten criteria including (Attendance, Conduite, neatness of dress, Ability, Improving the results achieved, Self-development, Quality, Atitude, Leadership, Teamwork), the final result of data processing using the SMART method is in the form of ranking of the results obtained by each employee.